Effect of Sports Massage Manipulation on Pain Intensity After Eccentric Exercise - Nurmaya, Ika; Roepajadi, Joesoef; Susanto, Indra Himawan; Nugraha, Testa Adi; Fikri, Muhammad Dzul (PHEDHERAL, 2023)
The purpose of this study was to analyze the effect of sports massage manipulation which is often used as passive recovery by measuring pain intensity using a visual analog scale (VAS) after eccentric exercise. This type of research is quantitative, with a quantitative descriptive design using a questionnaire (VAS), and data analysis method from examining pain intensity before and after manipulation of massage therapy. 54 athletes at the Indonesian National Sports Committee (KONI) in the Sidoarjo district participated as subjects. Using the Descriptive Statistical test before and after the massage therapy manipulation was carried out using the table or graphic diagram method, and the data obtained would be processed using SPSS for Windows v.22. It shows the mean (average) results of respondents' answers from respondents' answers about perceived pain intensity. From the results of testing the normal distribution of data using the Kolmogorov-Smirnov normality test, and then using the Wilcoxon test and the result was that there was a difference between pre and post-giving sport massage after eccentric exercise on pain intensity. From this study, it was concluded that giving sports massages had an effect on reducing pain intensity after eccentric exercise